2015
DOI: 10.1021/es504600q
|View full text |Cite
|
Sign up to set email alerts
|

Can Producing Oil Store Carbon? Greenhouse Gas Footprint of CO2EOR, Offshore North Sea

Abstract: Carbon dioxide enhanced oil recovery (CO2EOR) is a proven and available technology used to produce incremental oil from depleted fields while permanently storing large tonnages of injected CO2. Although this technology has been used successfully onshore in North America and Europe, there are currently no CO2EOR projects in the United Kingdom. Here, we examine whether offshore CO2EOR can store more CO2 than onshore projects traditionally have and whether CO2 storage can offset additional emissions produced thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 14 publications
(54 reference statements)
0
28
0
Order By: Relevance
“…Conventionally, operators aim to maximize both the amount of oil recovered and the amount of CO 2 recovered (rather than CO 2 stored) per tonne of CO 2 injected; between 1.1 and 3.3 barrels (bbl) of oil can be produced per tonne of CO 2 injected under conventional operation and within the constraints of natural reservoir heterogeneity 49 . However, in principle-and depending on operating conditions and project type-CO 2 -EOR can be operated such that, on a life-cycle basis, more CO 2 is injected than is produced upon consumption of the final oil product 50 .…”
Section: Conventional Utilization Pathwaysmentioning
confidence: 99%
“…Conventionally, operators aim to maximize both the amount of oil recovered and the amount of CO 2 recovered (rather than CO 2 stored) per tonne of CO 2 injected; between 1.1 and 3.3 barrels (bbl) of oil can be produced per tonne of CO 2 injected under conventional operation and within the constraints of natural reservoir heterogeneity 49 . However, in principle-and depending on operating conditions and project type-CO 2 -EOR can be operated such that, on a life-cycle basis, more CO 2 is injected than is produced upon consumption of the final oil product 50 .…”
Section: Conventional Utilization Pathwaysmentioning
confidence: 99%
“…As EOR can provide important stimulation for CCS deployment by reducing the overall costs of CO 2 capture and transport, thereby reducing the investment risk [41], it is critical to attract this EOR market with a low CO 2 price [29]. Although CO 2 -EOR oshore has yet to be done in the North Sea, studies have shown the feasibility and benets that could be brought on by its deployment [42,43,44,45].…”
Section: An Investment Decisionmentioning
confidence: 99%
“…The term negative emissions is also sometimes used to refer to CCS applied to fossil fuels, particularly in papers within the field of enhanced oil recovery (EOR). 28,29,30 In EOR, CO 2 is used to extract otherwise unrecoverable oil from otherwise depleted oil fields. Some EOR studies label the balance of CO 2 (CO 2 trapped in the geological formation minus CO 2 released when oil is combusted) negative emissions, regardless of the origin of the CO 2 , which, in most cases, is either extracted from natural formations or from the flue gas from the combustion of fossil fuels.…”
Section: Avoided Emissions and Enhanced Oil Recoverymentioning
confidence: 99%